Unconventional Monetary Policy Rules in a TANK Model - Galoci, Peter; Potužák, Pavel; Chytil, Zdeněk, 1949-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
The thesis examines the impact of unconventional monetary policy rules based on large purchases and sales of financial assets on the welfare of economic agents, comparing them to their conventional counterparts, both at and outside the zero lower bound, using the loss function evaluation approach. For this purpose, a representative-agent medium-scale New Keynesian DSGE model, encompassing multiple extensions, such as financial frictions and habit formation, is expanded to include two types of agents facing various borrowing constraints, who hold real money balances from which they derive utility. The expanded model exhibits standard TANK dynamics, which is used to evaluate the loss functions. The results suggest that the use of unconventional monetary policy rules in conjunction with conventional ones can enhance the stabilization capabilities of central banks, regardless of whether the zero lower bound is binding or not.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses